A comprehensive quality evaluation method of Corydalis yanhusuo by HPLC fingerprints, chemometrics, and correlation analysis. Issue 10 (31st March 2021) - Huang, Wei; Pan, Yan; Jiang, Huijie; Chen, Yi; Hu, Linshui; Zhang, Hui; Yan, Jizhong
Abstract: A novel quality evaluation method of Corydalis yanhusuo was established by researching the high‐performance liquid chromatography behavior of alkaloids under different buffer solutions and exploring the correlation between alkaloids in C. yanhusuo . The retention times of tetrahydropalmatine and corydaline were significantly influenced by pH, while the peak shape was affected by buffer types and ionic strength. The resolution of compounds in fingerprint was satisfactory under acetonitrile–0.2% phosphoric acid buffer (adjusted pH to 5.0 with triethylamine). Twelve common peaks were found by comparing 20 batches of C. yanhusuo fingerprints, and three tertiary alkaloids and four quaternary alkaloids were identified. The fingerprints were analyzed by similarity analysis, hierarchical cluster analysis, principal component analysis, and partial least squares discriminant analysis. All samples were divided into three groups, and the contents of dehydrocorydaline and coptisine from Zhejiang province were relatively higher than other origins. There were six components performing more contributions to the quality of C. yanhusuo . The correlations between alkaloids were conducted by Pearson correlation analysis and mathematical model analysis. The content correlation between palmatine and berberine was y =  0.28 x 2   +  0.03 x +  0.03, and the dehydrocorydaline and coptisine was y = − 7.54/(1  +  ( x/ 0.14) 0.5 )  +  2.61. The established mathematical model of alkaloids provided a guiding significance for the quality control of C. yanhusuo .